Evaluation of an Alternative Staining Method Using SYTO 13 to Determine Reticulated Platelets - Hille, Laura; Cederqvist, Marco; Hromek, Julia; Stratz, Christian; Trenk, Dietmar; Nührenberg, Thomas G. (Thrombosis and Haemostasis, 2019)
Reticulated platelets reflect the rate of platelet turnover and represent the youngest circulating platelets in peripheral blood. Reticulated platelets contain residual ribonucleic acid (RNA) from megakaryocytes which is lost in a time-dependent manner and can be transcribed into proteins even in the absence of a nucleus. An increased proportion of reticulated platelets is associated with higher platelet reactivity, cardiovascular events and mortality. At present, a fully automated assay system (SYSMEX haematology analyser) is available for analysis. This method, however, is not suitable for extended laboratory investigations like subsequent cell sorting. Flow cytometry analysis after staining with thiazole orange (TO) is frequently used in such settings despite several limitations. Here, we describe a new assay for determination of reticulated platelets by flow cytometry using the nucleic acid staining dye SYTO 13 and compare it with SYSMEX and TO staining as current standards. A significant correlation between immature platelet fraction (IPF) determined by SYSMEX XE-2100 analyser and results obtained with the SYTO 13-based assay was observed (r = 0.668, p < 0.001) which was stable during a reasonable time period. In contrast, the correlation between TO staining and IPF was weaker (r = 0.478, p = 0.029) and lost after 90 minutes of staining. SYTO 13 staining of platelets enabled sorting of RNAlow and RNArich platelets which was confirmed by RNA quantification of sorted platelets. Except for fixation of platelets, sorting of these platelet sub-populations was stable under various experimental settings. In summary, determination of reticulated platelets with the new SYTO 13 assay offers distinct technical advantages enabling further laboratory processing.
Keywords: reticulated platelets; immature platelet fraction; staining